2018
DOI: 10.3382/ps/pex298
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary vitamin C, vitamin E, and alpha-lipoic acid supplementation on the antioxidant defense system and immune-related gene expression in broilers exposed to oxidative stress by dexamethasone

Abstract: Vitamin C, vitamin E, and alpha-lipoic acid (ALA) are potent nutritional antioxidants, which are important for enhancing immunity. This study compared the effects of supplementation with vitamin C, vitamin E, or ALA on the antioxidant defense system and the expression of immune-related genes under oxidative stress induced by dexamethasone (DEX) in broilers. In total, 240 one-day-old female Recessive White Rock chickens were assigned randomly to either a basal diet (control group) or basal diet supplemented wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
72
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 58 publications
9
72
0
3
Order By: Relevance
“…More important is that ALA administered alleviated the mitochondrial apoptotic pathway following TBI and made the prognosis improve significantly . Therefore, it was reasonably believed that ALA can alleviate oxidative stress‐induced apoptosis following TBI . However, the mechanism of it on brain injury has not yet been undefined.…”
Section: Discussionmentioning
confidence: 99%
“…More important is that ALA administered alleviated the mitochondrial apoptotic pathway following TBI and made the prognosis improve significantly . Therefore, it was reasonably believed that ALA can alleviate oxidative stress‐induced apoptosis following TBI . However, the mechanism of it on brain injury has not yet been undefined.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, there has been a growing number of investigations focusing on the effect of ALA supplementation on the antioxidant defense system in chickens. In female Recessive White Rock chickens (twenty-one-days-old), ALA (500 mg/kg diet) has been found to increase plasma SOD, GPx enzyme activities, and decrease plasma MDA activity [20]. Moreover, it has been demonstrated that dietary supplementation with 300 mg/kg ALA enhances the antioxidant capability and inhibits oxidative stress in liver and muscle in Ross male broiler chicks [48].…”
Section: Discussionmentioning
confidence: 99%
“…Since there was no technique available for separating the R form from the R/S mix, we did not consider the optical activity of ALA. The grower diet (22-42 days) ( Table 1) was formulated to meet National Research Council (NRC, 1994)-recommended requirements for all nutrients and according to the procedure described in our prior report [19], whereas the ALA diet was prepared by using a basal diet supplemented with ALA (500 mg/kg diet) based on a previous report [20]. The experimental treatment was performed based on our previous study but with minor modifications [19].…”
Section: Animal Care and Experimental Treatmentmentioning
confidence: 99%
“…It has been reported that curcumin does not only down-regulate pro-inflammatory cytokines to reduce local inflammation in the intestine, but also reduces systemic inflammation triggered by the release of lipopolysaccharide (LPS) into circulation [44,51,52]. Similar to curcumin, AA is capable of decreasing the expression of proinflammatory cytokines such as IL-1, IL-6, IL-12, TNF-α and IFN-γ [53,54], which is indicative of better intestinal health.…”
Section: Discussionmentioning
confidence: 99%